Students documenting textile fragments - Unidentified photographer (Colorado State University. Libraries, 2002)
Photograph of students documenting textile fragments from the collection during a class in 2002. Two students wearing face masks are seated at a table with textile fragments.
Keywords: Fashion -- History; Fashion -- Exhibitions